A whole cell fluorescence quenching-based approach for the investigation of polyethyleneimine functionalized silver nanoparticles interaction with Candida albicans - Tiwari, Atul Kumar; Gupta, Munesh Kumar; Narayan, Roger J.; Pandey, Prem C. (Frontiers in Microbiology, 2023)
The antimicrobial activity of metal nanoparticles can be considered a two-step process. In the first step, nanoparticles interact with the cell surface; the second step involves the implementation of the microbicidal processes. Silver nanoparticles have been widely explored for their antimicrobial activity against many pathogens. The interaction dynamics of functionalized silver nanoparticles at the biological interface must be better understood to develop surface-tuned biocompatible nanomaterial-containing formulations with selective antimicrobial activity. Herein, this study used the intrinsic fluorescence of whole C. albicans cells as a molecular probe to understand the cell surface interaction dynamics of polyethyleneimine-functionalized silver nanoparticles and antifungal mechanism of the same. The results demonstrated that synthesized PEI-f-Ag-NPs were 5.6 ± 1.2 nm in size and exhibited a crystalline structure. Furthermore, the recorded zeta potential (+18.2 mV) was associated with the stability of NPS and shown a strong electrostatic interaction tendency between the negatively charged cell surface. Thus, rapid killing kinetics was observed, with a remarkably low MIC value of 5 μg/mL. PEI-f-Ag-NPs quenched the intrinsic fluorescence of C. albicans cells with increasing incubation time and concentration and have shown saturation effect within 120 min. The calculated binding constant (Kb = 1 × 105 M−1, n = 1.01) indicated strong binding tendency of PEI-f-Ag-NPs with C. albicans surface. It should also be noted that the silver nanoparticles interacted more selectively with the tyrosine-rich proteins in the fungal cell. However, calcofluor white fluorescence quenching showed non-specific binding on the cell surface. Thus, the antifungal mechanisms of PEI-f-Ag-NPs were observed as reactive oxygen species (ROS) overproduction and cell wall pit formation. This study demonstrated the utility of fluorescence spectroscopy for qualitative analysis of polyethyleneimine-functionalized silver nanoparticle interaction/binding with C. albicans cell surface biomolecules. Although, a quantitative approach is needed to better understand the interaction dynamics in order to formulate selective surface tuned nanoparticle for selective antifungal activity.